Plasma amyloid beta predicts conversion to dementia in subjects with mild cognitive impairment: The BALTAZAR study. Issue 12 (20th February 2022) - Hanon, Olivier; Vidal, Jean‐Sébastien; Lehmann, Sylvain; Bombois, Stéphanie; Allinquant, Bernadette; Baret‐Rose, Christiane; Tréluyer, Jean‐Marc; Abdoul, Hendy; Gelé, Patrick; Delmaire, Christine; Blanc, Fredéric; Mangin, Jean‐François; et al.
Abstract: Introduction: Blood‐based biomarkers are the next challenge for Alzheimer's disease (AD) diagnosis and prognosis. Methods: Mild cognitive impairment (MCI) participants (N = 485) of the BALTAZAR study, a large‐scale longitudinal multicenter cohort, were followed‐up for 3 years. A total of 165 of them converted to dementia (95% AD). Associations of conversion and plasma amyloid beta (Aβ)1‐42, Aβ1‐40, Aβ1‐42 /Aβ1‐40 ratio were analyzed with logistic and Cox models. Results: Converters to dementia had lower level of plasma Aβ1‐42 (37.1 pg/mL [12.5] vs. 39.2 [11.1], P value = .03) and lower Aβ1‐42 /Aβ1‐40 ratio than non‐converters (0.148 [0.125] vs. 0.154 [0.076], P value = .02). MCI participants in the highest quartile of Aβ1‐42 /Aβ1‐40 ratio (>0.169) had a significant lower risk of conversion (hazard ratio adjusted for age, sex, education, apolipoprotein E ε4, hippocampus atrophy = 0.52 (95% confidence interval [0.31–0.86], P value = .01). Discussion: In this large cohort of MCI subjects we identified a threshold for plasma Aβ1‐42 /Aβ1‐40 ratio that may detect patients with a low risk of conversion to dementia within 3 years.